Experiencing Traumatic Violence: An Interpretative Phenomenological Analysis of One Man’s Lived Experience of a Violent Attack Involving a Knife - Zoe Partington; R. Stephen Walsh; Danielle Labhardt (Behavioral Sciences)
A review of the violent knife crime literature suggests that the experiential perspective is one which has not been addressed in academic study. The research presented hereafter aims to address this literary gap and generate transferable knowledge relevant to the lived experience of violent knife crime. The experiential study of the single case within psychological research involves detailed examination of a particular event. Participant ‘J’ is the survivor of an extremely violent attack, involving the use of a knife, in his own home. J’s experience was analysed using Interpretative Phenomenological Analysis with reference to elements of the lifeworld: temporality, spatiality, intersubjectivity, and embodiment. Three themes were identified: 1. switching from past to present tense when relaying traumatic experience; 2. The presence of redemption sequences; and 3. making sense as a temporal process, which included an additional two subthemes—‘The long journey’ and ‘Seeking belongingness’. This case emphasises that the traumatic event is conceptualised as one part of a longer journey towards recovery, and that recovery itself is central to the experience of violent knife crime. Finally, the need to understand recovery as temporal process highlights the need to provide victims with appropriate support in order to avoid negative outcomes.